Ferri Coll, José M.ª, Rubio Cremades, Enrique, y Thion Soriano-Mollá, Dolores (eds.), Azorín. La invención de la literatura nacional. Madrid: Iberoamericana Editorial, 2019 - López Viñas, Maila (Anales de Literatura Española, 2020)
Reseña de: Ferri Coll, José M.ª, Rubio Cremades, Enrique, y Thion Soriano-Mollá, Dolores (eds.), Azorín. La invención de la literatura nacional. Madrid: Iberoamericana Editorial, 2019, ISBN:978-84-9192-081-6, 384 pp.